(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2016)
Financial inclusion is one of the great initiated taken V. Venugopal Reddy, the governor of RBI in April 2015 in his annual policy statement and regarded technology adoption as an important and essential feature for attaining financial inclusion. Financial inclusion refers to providing financial services at affordable costs to vast sections of disadvantaged and low income groups. The payment banks, also known as niche banks, are the financial entities established by the RBI in November 2014. These entities can accept the deposits from the customer only upto Rs. 1 lakh and pay interest on the same. These banks are not allowed to lend money on credit to its customers and external parties as well as not allowed to issue plastic money i.e. debit and credit cards. The main objective behind setting up of payment banks is to support the scheme of financial inclusion by offering small saving accounts and payment or remittance services to low income household, small businesses and other unorganized sector entities. This research paper attempts to analyze whether the role played by these payment banks established by RBI is sufficient in strengthening the campaign of financial inclusion in India.